Tolerance of tetraselmis tetrathele to high ammonium nitrogen and its effect on growth rate, carotenoid and fatty acids productivity - Abd. Wahab, Farahin; Ikhsan, Natrah; Nagao, Norio; Md. Yusoff, Fatimah; Shariff, Mohamed; Banerjee, Sanjoy; Katayama, Tomoyo; Nakakun, Masatoshi; Koyama, Mitsuhiko; Nakasaki, Kiyohiko; Toda, Tatsuki (Frontiers Media, 2021)
Microalgae can use either ammonium or nitrate for its growth and vitality. However, at a certain level of concentration, ammonium nitrogen exhibits toxicity which consequently can inhibit microalgae productivity. Therefore, this study is aimed to investigate the tolerance of Tetraselmis tetrathele to high ammonium nitrogen concentrations and its effects on growth rate, photosynthetic efficiency (Fv/Fm), pigment contents (chlorophyll a, lutein, neoxanthin, and β-carotene), and fatty acids production. Experiments were performed at different ammonium nitrogen concentrations (0.31–0.87 gL−1) for 6 days under a light source with an intensity of 300 μmol photons m−2 s−1 and nitrate-nitrogen source as the experimental control. The findings indicated no apparent enhancement of photosynthetic efficiency (Fv/Fm) at high levels of ammonium nitrogen (NH+4-N) for T. tetrathele within 24 h. However, after 24 h, the photosynthetic efficiency of T. tetrathele increased significantly (p < 0.05) in high concentration of NH+4-N. Chlorophyll a content in T. tetrathele grown in all of the different NH+4-N levels increased significantly compared to nitrate-nitrogen (NO3-N) treatment (p < 0.05); which supported that this microalgal could grow even in high level of NH+4-N concentrations. The findings also indicated that T. tetrathele is highly resistant to high ammonium nitrogen which suggests T. tetrathele to be used in the aquaculture industry for bioremediation purpose to remove ammonium nitrogen, thus reducing the production cost while improving the water quality.